Social Sciences and Cultural Studies Issues of Language, Public Opinion, Education and Welfare - Lopez-Varela, Asuncion (IntechOpen, 2012)
This is a unique and groundbreaking collection of questions and answers coming from higher education institutions on diverse fields and across a wide spectrum of countries and cultures. It creates routes for further innovation, collaboration amidst the Sciences (both Natural and Social) and the Humanities and the private and the public sectors of society. The chapters speak across socio-cultural concerns, education, welfare and artistic sectors under the common desire for direct responses in more effective ways by means of interaction across societal structures.